Analisis Poster Film “Saya Nikahkan” Menggunakan Pendekatan Semiotika Roland Barthes - Rejeki, Amanda Sri; Pramudya, Juwita Oktaviani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2024)
Movie posters are often used as promotional media to communicate the content or conflict of the story contained in a movie. Various visual elements contained in the poster contain signs. These signs will later have a meaning that will try to convey to the audience. The science that studies signs is semiotics. Semiotics studies the theory of signs in the context of scenarios, images, texts or scenes in movies that can be interpreted. This research will discuss the analysis of the movie poster